THE INFLUENCE OF EXTERNAL AND INTERNAL FACTORS ON THE LEVEL OF ECONOMIC SECURITY OF AN ENTERPRISE - NASRULLAYEV, Ravan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to analyzing and assessing the influence of external and internal factors on the level of economic security of the enterprise, as well as identifying the most critical risks and threats.It is proven that in modern conditions of a turbulent environment, ensuring the economic security of enterprises is particularly relevant, as the stability and competitiveness of business entities directly depend on their ability to respond effectively to a complex array of external and internal challenges.It is established that the level of economic security of an enterprise is the result of a complex interaction of external and internal factors. It is determined that the external environment shapes the conditions for an enterprise's functioning, particularly through the country's economic situation, the level of competition, state regulation, access to financial resources, and the influence of global markets. Internal factors, in turn, determine the enterprise's ability to effectively respond to challenges, which include financial stability, quality of management, innovative potential, human resources, and the level of organizational culture.The results of the analysis revealed that the key threats to economic security include reduced solvency, supply instability, exchange rate fluctuations, increased production costs, and reduced demand for products. At the same time, timely identification of risks, implementation of a monitoring system, and use of adaptive management strategies can significantly reduce the impact of negative factors. It is substantiated that ensuring an adequate level of economic security for an enterprise requires an integrated approach that combines constant monitoring of the external environment with optimization of internal resources, thereby increasing the competitiveness and stability of the enterprise in a dynamic market.
Keywords: internal factors; external factors; economic security; competitive environment; enterprise; influencing factors